THE ANALYSIS OF HUMAN RESOURCES DEVELOPMENT STRATEGY OF WOMEN FARMERS' GROUPS (KWT) IN SINAR BULAN VILLAGE, BUKIT INTAN DISTRICT, PANGKALPINANG CITY - jennie rorensia; Nadiatus Sholiha, Iska; Eritawana (Universitas Indo Global Mandiri Palembang, 2024)
Objective: This study aims to analyze the Human Resource Development Strategy carried out by the Women Farmers Group (KWT) in Sinar Bulan Village, Bukit Intan District, Pangkal Pinang City which aims to develop the productivity of KWT members, improve the performance and creativity of KWT members and improve the quality of organizational human resources. And the purpose of this study is also to suggest that there needs to be an evaluation of the Human Resource Development Strategy to improve organizational performance. Design/Method/Approach: The method used in this research is a qualitative method, This study uses a case study that focuses on the HR development strategy in KWT Sinar Bulan Village . Data collection techniques use literature studies, especially by reading articles that have been published in various journals related to HR development strategies and related to Women Farmers Groups, Researchers also conduct data collection techniques by means of observation to the research location, then other data collection techniques are also by interview methods from informants totaling 7 people consisting of the KWT Chairperson, KWT Secretary, KWT Treasurer and 4 KWT members. The data analysis technique used in this study was SWOT analysis. Findings: The results of this study indicate that the good performance of some active members is due to having attended training and development, but there are several problems with the Human Resource Development Strategy in inactive members and the lack of awareness in advancing and developing KWT so that researchers suggest conducting several evaluations of several Human Resource Development Strategies in KWT Sinar Bulan through a SWOT analysis that has been made by researchers . Originality/Value: This research is based on the researcher having conducted an observation at the research location unintentionally, by observing the different characteristics of the members, the ineffective HR management system at the research location made the researcher interested in researching the problems that exist in KWT Sinar Bulan. Practical/policy implications : This research is expected to provide benefits to members because the researcher has provided some suggestions and evaluated the research location, it is expected to provide effective changes to the HR management strategy at the research location.